A Study on Successful Brand Promotion Strategy of Coway - Padmalini Singh; Divya S; Lim Chee Shan; Daisy Mui Hung Kee; Lee Zhen Wei; Hong Chin Yee; Mao Xinyu; Nuruldiana Binti Jamry; Oh Zi Jian; Nor Ramadhani Binti Arsathali; Nurul Erni Athirah Binti Kamaruzzaman (Journal of the Community Development in Asia (JCDA), 2021)
The innovation of industrial technology is growing rapidly every day. One of them is The Coway company which produce air purifier and water purifier, whose main vision is to preserve an environment. This company has branches in India and Malaysia. For our research study, we have considered consumer products such as air purifier and water purifiers with marketing communication channel which will affect public’s buying behavior on Conway products. There are various marketing promotion channels to be used by companies and however, the best way to reach the customers are always challenging. This study involves primary data through a survey and involves to identify the best promotion channels that the public in India and Malaysia would vote for. This study helps Coway to promote their products through best strategy so that they can increase the market share through consumers feedback in terms of promotion strategies.